Destination characteristics of modest fashion city: Tourism marketing perspectives - Bastaman, Aam; Osman, Ismah; Rimbawati, Putri Rakhmadhani Nur (Jurnal Manajemen dan Pemasaran Jasa, 2023)
Purpose – Cities aim to differentiate themselves and project a favorable image to maintain a competitive edge in today's tourism industry, which this endeavor includes the city of Bandung. Bandung has undergone certain facelifts within its metropolitan areas to establish city uniqueness concentrating on fashion and design. Hence, this study aims to examine Bandung’s brand image and personality, emphasizing the branding of Bandung as a modest fashion city and its impact on business, fashion, culture, and tradition. Design/methodology/approach –Utilizing qualitative research, this research narrates the findings of in-depth interviews with selected informants, specifically, the locals and the tourists, in addition to the use of desk research, and observation. Thus, it analyzes the perception of the tourists and local people concerning Bandung’s aptitude as a modest fashion city and its capacity to capture the target market, locally and abroad. Findings – Business tourism is crucial to Bandung’s development and vision to be a modest fashion destination. Bandung has the potential to achieve the vision due to its people’s outstanding creativity. It makes an expansion towards a destination concentrating on modest fashion viable. Consequently, the city boasts a thriving textile industry, a solid local administration, vibrant local entrepreneurship, a strong fashion sense built on tertiary education, and an excellent collaborative relationship between the local community, academicians, industry, and the government. Research limitations/implications – This study unearth the preliminary research phase for a new city trademark. Nevertheless, quantitative and longitudinal research is required. Practical implications – The study discusses the implications for developing a consistent destination branding strategy by analyzing the initial stages of Bandung as a modest fashion destination Originality/value – The study presents specific recommendations to tourism and hospitality practitioners for widening Bandung’s destination image to capitalize on the city's art and cultural heritage. It is also of interest to tourism researchers since it contributes methodologically to the literature on place branding through projective methodologies. Keywords: Bandung city; Destination image; Modest fashion tourism; Qualitative Research;